Wagar and Motley “Archaic” Vestiges: A Postmodernist Reading of Contemporary Somali Fiction - Nyongesa, Andrew (Journal of Literary Studies, 2022)
The advent of the modernist dream resulted in the universalisation of culture, which entails deliberate effort to abandon traditional ways of life that foster difference and instead embracing national cultures to bring different communities together. Colonialism in the Horn of Africa, for instance, brought different Cushitic communities under single political entities and most of them adopted Islam to find a common ground. Other communities in East Africa had to convert to Christianity to find a universal cultural bridge. This has resulted in the assumption that most African peoples are homogeneous given that past traditions that elevated difference have been eradicated by unifying factors such as modern states and conventional religions such as Islam and Christianity. A critical reading of some literary texts, however, demonstrates that such claims are partly unfounded because there exist aspects of pre-Islamic Somali religion along with the fundamental beliefs of Islam, which bolster difference. This article is a postmodernist reading of selected contemporary Somali fiction to investigate the influence of pre-Islamic Somali religion on contemporary Somali culture. Using the ideas of Jacques Derrida and Joseph Campbell, the study demonstrates the impact of myth and the ancient traditions on migration and contemporary culture in Nadifa Mohamed’s Black Mamba Boy and Nuruddin Farah’s Secrets.